Lead Reduction on Polluted Water and Sediment through The Use of Anadara granosa shells and Monostroma nitidum Biological Filters - Mochammad Amin Alamsjah (Department of Aquaculture, 2023)
Industrial waste water treatment holds a very vital role in filtering toxic materials and improving the quality of industrial waste water before being released into public waterways, so that the water ecosystem balance can be maintained. This study aims to identify Pb concentration on polluted water and sediment from an offshore oil drilling area near Camplong Beach, Madura, and also make efforts to find out the potential Anadara granosa shells and Monostroma nitidum seaweed biofilters that exist in that place so as to suppress the adverse effects of toxic materials that arise. The method used was experimental research design that aims to systematically obtain information to describe a lead concentration on polluted water and sediment, and also evaluate the presence of A. granosa shells and M. nitidum as a potential biological filter. The results of the analysis of lead in A. granosa shells, M. nitidum biofilter, water, and sediment indicated that there was a significant correlation, where the shells of A. granosa and M. nitidum can absorb lead until 36.59% and 8.79%, respectively, from which the initial concentrations of lead in sediment and water were 5.57±1.58 and 0.004±0.001 mg/kg respectively. The existence of algicidal substances of HDTA, ALA, and ODTA from M. nitidum can suppress the growth of dinoflagellatas of Chattonella marina. The quantification analysis of fatty acid composition showed that M. nitidum is dominated by PUFA as much as 66% of total fatty acid, and has algicidal substances of HDTA, ALA, and ODTA of 61.53 mg/100 g.